Employing Simulation Models for Addressing Issues in Warehouse Systems - Grzęda, Anna; Żuchowicz, Patryk (Wykorzystanie modeli symulacyjnych do rozwiązywania problemów w układach magazynowych, 2023)
Aim: The aim of this article was to investigate whether the appropriate arrangement of products on warehouse shelves significantly affects order fulfillment time, and whether the use of computer simulation can be helpful in warehouse management. Methodology: A series of simulation studies was conducted using FlexSim software, version 22.2.2. The simulation involved examining which of the three selected variants of product arrangement in the warehouse was most advantageous. Each case was analysed in terms of such parameters as: order fulfillment time, revenue, number of undelivered pallets, and financial outcome. Results: The conducted simulation studies allowed for the selection of the optimal strategy for product placement in the warehouse. Implications and recommendations: In view the conducted research, it can be concluded that changing the method of arranging goods on warehouse shelves can significantly improve the efficiency and effectiveness of warehouse processes. Furthermore, the results of the analysis of warehouse processes using simulation confirmed that it is an effective decision support tool for optimising warehouse processes.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 136-142
Keywords: warehouse management; product storage; product placement; simulation models; discrete event simulation; gospodarka magazynowa; składowanie produktów; rozmieszczenie produktów; modele symulacyjne; symulacja zdarzeń dyskretnych